Damage of bamboo and wooden materials based on linear elastic fracture mechanics in garden design (Fracture and Structural Integrity, 2015)
Bamboo and wood are the most widely applied and the oldest natural structural materials in the world. Currently, worldwide output of wooden material is 1 billion ton, almost the same as steel. Most of them are used as structure, such as load carrying girder, scaffold, floor and support. Wooden materials and bamboo materials with clear microstructure are composite biomaterials which can be studied under multiple scales. Irregular evolution behaviors of initial defects or damage during loading determines macro mechanical behavior of wooden and bamboo materials. Taking wood and bamboo as test materials, this study explored mechanical characteristics and damage crack behavior of wood and bamboo as well as toughening mechanism.
Keywords: Wooden material; Bamboo material; Damage and crack; Strengthening and toughening mechanism